Quantifying and Characterizing Phonetic Reduction in Italian Natural Speech - Loredana Schettino; Francesco Cutugno (Languages)
The main purpose of this study is to test a method for the analysis of phonetic variation in natural speech. The method takes into account the continuous nature of the speech flow and allows for the investigation of the systematic variation phenomena that occur in the speech net of the cross-word coarticulation phenomena that are expected in connected speech. We will describe some of the most frequent phonetic variation patterns that may be observed in the speech chain seen as a sequence of syllables, in relation to internal syllabic structure and lexical stress. The present study concerns speech data from the Italian section of the NOCANDO corpus. The data consist of about 1000 syllables extracted from monological speech from different speakers. In two different analysis layers, we attempted to align the “phonological” expected form and observed realisation. The results of this attempt led to the definition of syllabic deletion, substitution, or insertion when the alignment fails. The proposed method provides insight into the phonetic variation processes that can systematically occur in natural speech with relation to specific linguistic structures; in particular, unstressed syllables are most likely to undergo variation phenomena, and systematic differences concern the syllabic position of the segmental change, in that the presence of lexical stress prevents vowel deletion or centralization, but allows for onset changes (such as consonant cluster simplification or lenition).